2021
DOI: 10.1051/e3sconf/202128503002
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological peculiarities of microalgae chlorella production and use in poultry

Abstract: The current paper presents data on the features of biotechnological cultivation of chlorella microalgae strain IFR C-111 on different nutrient media. Evaluation of the influence of the illumination period on the rate of biomass growth on the selected nutrient medium has also been presented. There are materials of microalgae suspension influence the effect on the biological resource’s potential of quails.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…To solve this problem, electrohydraulic tillage was carried out based on the electrohydraulic effect of Yutkin [1]. It was previously shown that during electrohydraulic crushing of rocks and other non-metallic materials, many chemical elements and their compounds that are part of these rocks pass into the water in the form of soluble compounds in amounts reaching 90-95% of their mass content in the original material [6].…”
Section: Vitaminsmentioning
confidence: 99%
See 1 more Smart Citation
“…To solve this problem, electrohydraulic tillage was carried out based on the electrohydraulic effect of Yutkin [1]. It was previously shown that during electrohydraulic crushing of rocks and other non-metallic materials, many chemical elements and their compounds that are part of these rocks pass into the water in the form of soluble compounds in amounts reaching 90-95% of their mass content in the original material [6].…”
Section: Vitaminsmentioning
confidence: 99%
“…They cause significant damage by slowing down the growth and development of juvenile fish, reducing the resistance of their body to the effects of environmental factors and pathogens, as well as partial death of fish. To prevent this condition, artificial vitamins are used [6], as scientific studies have shown. Synthetic vitamins are "dead" substances that do not carry any energy, they are practically not absorbed by the body.…”
Section: Introductionmentioning
confidence: 99%